Reduced Reproductive Success of Western Baltic Herring (Clupea harengus) as a Response to Warming Winters - Polte, Patrick; Gröhsler, Tomas; Kotterba, Paul; von Nordheim, Lena; Moll, Dorothee; Santos, Juan; Rodriguez-Tress, Paco; Zablotski, Yury; Zimmermann, Christopher (Frontiers in Marine Science, 2021)
Shallow estuaries, bays, and lagoons are generally considered hot spots of ocean productivity that often adjust rapidly to seasonal variations in atmospheric temperatures. During spring when biological reproductive processes begin in the temperate zones, regional climate variability can be immense and uncovering a non-linear biological response, such as fish recruitment to changing temperature regimes might be challenging. Using herring as a paradigm for a response of coastal spring productivity to regional climate drivers, we demonstrated how the annual timing of spawning periods can significantly affect the reproductive success of spring-spawning herring (Clupea harengus) in the western Baltic Sea. An investigation of spawning phenology in consecutive years indicated a temperature threshold range of 3.5–4.5 °C triggering initial spawning in the coastal zone. Based on this finding, we analyzed the timing of larval hatching peaks, larval survival and recruitment to the adult population relative to multi-decadal time-series of seasonal sea-surface temperatures. The results revealed that the late seasonal onset of cold periods the corresponding elongation of the period where larvae hatch from the eggs and early larval hatching peaks significantly reduced larval production in a coastal nursery area and finally lead to a reduced abundance of juveniles in the entire distribution area. Using a combination of field research and time series analysis, we presented precedence for shifting regional winter regimes providing a present-day stressor to reproductive capacity of a central component of the coastal food web.